Notes About Some Elements of the Content of a Due Collective Process in Peru - Glave Mavila, Carlos (2017)
Given the lack of regulation about the protection of collective rights in Peru, the main goal of this investigation is to show what should be some elements of the content of a due collective process. Thus each of its elements is studied taking into account the Peruvian jurisprudence and legislation.